OPTIMALISASI EDUKASI KESEHATAN BERBASIS MEDIA SOSIAL: STUDI IMPLEMENTASI PADA POSYANDU CEMARA JATIRANGGON - Dewi Ambarsari; Alifiah Ghaniyyu Widyaningrum; Prastika Indriyanti (Jurnal Abdi Insani, 2026)
Social media has strong potential as a means of community health education due to its rapid, easy, and interactive distribution. As the frontline provider of maternal and child health services, Posyandu (Integrated Health Posts), (Posyandu), needs to utilize digital media to improve public health literacy. However, limited skills among cadres pose a major challenge, resulting in less engaging content and inability to optimize public participation. Therefore, it is necessary to strengthen the cadres' capacity to create effective, creative content based on social media and websites. This community service activity aims to improve the skills of 10 Posyandu Cemara Jatiranggon cadres in managing digital media through training in creating engaging and relevant educational content for the surrounding community to optimally support sustainable health services. The activity methods included outreach, technical training, hands-on practice, gradual mentoring, and evaluation using pre- and post-tests with a Likert scale. The assessment instruments focused on cadres' understanding of design principles, use of the Canva application, and ability to compose health messages and materials communicatively. Based on the evaluation results, the average cadre knowledge score increased from 2.17 (less understanding category) in the pre-test to 3.93 (understanding category) in the post-test. There was an 81.11% increase in competency, with the highest increase in the ability to use the website for reporting at 137.50%. Cadres are now able to produce visual content and manage the integrated health post website independently. This indicates an increase in cadre knowledge of creative and informative content. The training enhanced cadres' understanding of the importance of educational content to attract residents to Posyandu. The content uploaded was also more varied and interactive, consistently delivered each week. In conclusion, the creative content training proved effective in increasing cadres' capacity while significantly expanding the reach of general social media-based health education.